Comparative study of different meloxicam generic products with the brand product - Myasar Al-kotaji (College of Pharmacy / Mustansiriyah University, 2019)
This study aims to evaluate different products of meloxicam Table; Five meloxicam immediate-release generic products (15 mg Tables) were compared with the innovator, reference product, (Mobic®, Boehringer) to find the interchangeable product with the innovator product. Different physical tests were conducted including weight uniformity, thickness, diameter, hardness, friability and disintegration test. In addition, prediction of in-vivo behavior was assessed by measuring the dissolution profile of meloxicam for all the products. Similarity factor (f2) was calculated to compare between the dissolution profile of the generic products with the dissolution profile of innovator product. The results revealed that all the studied products are complied with the British Pharmacopoeia requirements. However, not all of them showed similar in-vitro profile to the brand product.  Four out of five generic products, included in this study, showed similarity in dissolution profile to the brand one, which indicates possible bio-equivalency, with the advantages of money saving of using such generic products. One generic product showed similarity factor less than 50, which might give an indication that this generic product is not capable to be bioequivalent with the brand (innovator) product. Overall, this study can be considered an important applicable study that gives an indication about the in-vivo performance of different products. In addition, the study demonstrates the applicability of a simple in-vitro dissolution study as a surrogate way of assessing product bioavailability instead of an expensive and complicated in-vivo bioequivalent study.